Pengaruh Motivasi Belajar, Religiusitas dan Integritas Mahasiswa Terhadap Perilaku Kecurangan Akademik (Studi Pada Mahasiswa Akuntansi Universitas Islam Malang dan Universitas Islam Negeri Maulana Malik Ibrahim Malang Angkatan 2018) - Yolanda Murika S; Moh. Amin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine the effect of student motivation, religiosity and integrity on academics. The researcher determined that the students of the Islamic University of Malang and the State Islamic University of Maulana Malik Ibrahim were the population. Meanwhile, the researcher used the slovin formula in determining the sample with 80 students as respondents. The research method used is primary data quantitative research with questionnaire data collection techniques using a 5-point Likert scale. The data analysis method used is multiple linear regression analysis using SPSS tools. The results of this study indicate that learning motivation, religiosity and integrity simultaneously affect academic fraud. Partially, motivation has a negative effect on academic fraud, religiosity has a negative effect on academic fraud, and student integrity has a negative effect on academic fraud.Keywords : Learning motivation, religiosity, student integrity and academic cheating.